The Prevalence and Significance of Leukopenia Induced by Intravenous Iron Therapy in a Large Cohort of Females with Iron Deficiency Anemia (IDA) : Leukopenia Induced by Intravenous Iron Therapy in Females with Iron Deficiency Anemia - De Sanctis, Vincenzo; Soliman, Ashraf T; Yassin, Mohamed A (Acta Biomedica Atenei Parmensis, 2022)
Introduction: Iron deficiency anemia (IDA) is the most common cause of anemia in both developed and developing countries. Leukopenia is an infrequent side effect of iron therapy reported in the literature as sporadic cases. Objective: To assess the prevalence of leukopenia, neutropenia and/or lymphocytopenia and its possible clinical impact if any, after intravenous iron therapy in adult patients with IDA. Patients and Methods: This is a retrospective study conducted in Hamad Medical Corporation, Doha (Qatar). The clinical and biochemical data of 1.567 females (mean age: 29.5 years) with IDA who attended the Hematology Clinic and were treated with intravenous (i.v.) iron therapy were collected and analysed. Complete and differential blood counts and iron profile were studied before and after i.v. iron therapy. In addition, cases who developed infections during the time of leukopenia were noted and checked for possible complications. Results: 30 cases (1.91%) developed leukopenia,15 cases (0.95%) developed neutropenia and 12 cases (0.76%) developed lymphocytopenia. All had normal white blood cell counts before treatment. Two patients (6.66%) had infection. One had upper respiratory tract infection and the other had urinary tract infection, the latter was treated with antibiotics. There was no reported other infection during or after i.v. iron therapy. Conclusions: Leukopenia in form of neutropenia or lymphocytopenia may occur as a side effect of i.v. iron therapy, however, its clinical significance appears to be limited.